2020
DOI: 10.1038/s42003-020-01143-5
|View full text |Cite
|
Sign up to set email alerts
|

Host-parasite tissue adhesion by a secreted type of β-1,4-glucanase in the parasitic plant Phtheirospermum japonicum

Abstract: Tissue adhesion between plant species occurs both naturally and artificially. Parasitic plants establish intimate relationship with host plants by adhering tissues at roots or stems. Plant grafting, on the other hand, is a widely used technique in agriculture to adhere tissues of two stems. Here we found that the model Orobanchaceae parasitic plant Phtheirospermum japonicum can be grafted on to interfamily species. To understand molecular basis of tissue adhesion between distant plant sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 43 publications
(68 reference statements)
3
33
0
Order By: Relevance
“…However, it was recently proven that plants from different families even distant ones can be grafted successfully ( Notaguchi et al, 2020 ); phylogenetic proximity or similarity in the vascular anatomy of the grafting partners does not seem to result always in grafting realization ( Wulf et al, 2020 ). It is shown that grafting is facilitated by the action of genes such as cellulases that help the reconstruction of cell walls; these genes can facilitate tissue adhesion and promote plant grafting ( Kurotani et al, 2020 ; Notaguchi et al, 2020 ). If plants possess or are bred to possess such genes in abundance, interfamily barriers in grafting could be lifted and grafting technology can be expanded to deliver more chimeric plants that will take advantage of both distantly related partners’ advantages.…”
Section: Grafting Technics and Long-distance Signalingmentioning
confidence: 99%
“…However, it was recently proven that plants from different families even distant ones can be grafted successfully ( Notaguchi et al, 2020 ); phylogenetic proximity or similarity in the vascular anatomy of the grafting partners does not seem to result always in grafting realization ( Wulf et al, 2020 ). It is shown that grafting is facilitated by the action of genes such as cellulases that help the reconstruction of cell walls; these genes can facilitate tissue adhesion and promote plant grafting ( Kurotani et al, 2020 ; Notaguchi et al, 2020 ). If plants possess or are bred to possess such genes in abundance, interfamily barriers in grafting could be lifted and grafting technology can be expanded to deliver more chimeric plants that will take advantage of both distantly related partners’ advantages.…”
Section: Grafting Technics and Long-distance Signalingmentioning
confidence: 99%
“…We recently uncovered a key role of the GH9B3 clade of β-1,4-glucanases in cell-cell adhesion at the graft junction (Kurotani et al 2020;Notaguchi et al 2020). β-1,4-glucanases probably target cellulose in cell walls, and the overexpression of the β-1,4-glucanase gene promotes graft efficiency in Arabidopsis (Notaguchi et al 2020).…”
Section: Effect Of Cellulases On the Adhesion Of Nb Ivgmentioning
confidence: 99%
“…Using this system, we first showed that exogenous treatment with cellulases promotes graft adhesion. Given that numerous candidate genes related to grafting have been identified through recent transcriptome analyses (Chen et al 2017;Cookson et al 2014;Kurotani et al 2020;Li et al 2016;Liu et al 2016;Melnyk et al 2015;Notaguchi et al 2020;Wang H et al 2019;Xie et al 2019), methods for evaluating graft efficiency are required to test the roles of such genes. The IVG system can be applied to test the effect of genetic lines, environmental factors, and chemical treatments.…”
Section: Effect Of Cellulases On the Adhesion Of Nb Ivgmentioning
confidence: 99%
See 2 more Smart Citations